El sistema flotante como alternativa para la produccion de plantines de Lisianthus (Eustoma grandiflorum L.) - Barbaro, L.A.=700 1 Karlanian, M.A.; Morisigue, D.
(Es, En)
Ilus., 27 ref.
Keywords: CULTIVO HIDROPONICO; EUSTOMA GRANDIFLORUM; PRODUCCION; PLANTULAS; ARGENTINA; AGRISCIENTIA